A Note on the Labor Market Effects of Remittances in Latin American and Caribbean Countries: Do Thresholds Exist?. (March 2014) - Jackman, Mahalia
<x xml:space="preserve">Abstract</x> The labor market effects of remittances have long been examined in the empirical literature. To date, the results have been mixed: some authors observe a negative association between remittances and unemployment while others report that remittances increase unemployment. This study empirically examines the impact of remittances on unemployment using macroeconomic data for a sample of 18 Latin American and Caribbean countries. Specifically, the study tests whether there is a nonlinear relationship between the variables. Results suggest that when the remittance‐to‐GDP ratio is low, remittances have a positive and significant impact on unemployment. However, as they increase, remittances are negatively associated with unemployment. This suggests the possibility that estimations based on the assumption of a linear relationship between remittances and labor may mask the true relationship between the variables.